(untitled) (TEST Antologia di Diritto Pubblico, 2026)
The essay examines the interpretation of administrative acts from the perspective of administrative judicial proceedings, highlighting the relationship between the judge’s hermeneutic activity and procedural rules. An analysis of the case law reveals two opposing trends: a “pervasive” approach, which leads the judge toward integrative or manipulative readings of the content of the act, and an “abstentionist” approach, which avoids classifying the administrative measure, thereby generating significant uncertainty in terms of judicial protection. A system-consistent interpretation, by contrast, should be grounded in the necessary reference to the administrative procedure, understood as the objective and transparent context within which the administrative act acquires meaning.